“We’re all in it together”: uniting a diverse range of professionals and people with lived experience within the development of a complex, theory-based paediatric speech and language therapy intervention - Lucy Rodgers; Nicola Botting; Natalie Abdo; Meriem Amer-El-Khedoud; Emma Baker; Sophie Franks; Dave Harford; Patrycja Salimi-Tabar; Laura Temple; Ros Herman (Research Involvement and Engagement)
Abstract Background It is increasingly commonplace to involve relevant professionals and people with lived experience within healthcare research. Although valuable case studies regarding such involvement exist, there is currently a paucity of case studies highlighting the professional and personal impacts of uniting a diverse group of professionals and people with lived experience within the development of new, theory-based interventions. The aim of this paper is to provide insight into the impacts of involving a diverse range of individuals, unified within a single steering group, within the development of a new, theory-based, paediatric speech and language therapy intervention (“Supporting Words and Sounds” - SWanS). By describing the involvement process in detail and providing our personal insights, we hope our recommendations will be of use to future healthcare researchers. Main body Our project steering group consists of two people with lived experience (an adult with Developmental Language Disorder-DLD, a parent of a child with DLD), three specialist NHS speech and language therapists (including one university lecturer with equality and diversity expertise), and two individuals working in the education sector (a specialist teacher and a bilingual educational support worker). Group members have been involved across the 4 phase intervention development process. Tools such as the PiiAF (Public involvement impact Assessment Framework) have guided our personal and professional reflections on our individual experiences of being in a diverse steering group responsible for developing a new and complex theory-based intervention. Conclusion We found that having a diverse range of people unified in a singular intervention development steering group had unexpected benefits. Learning from each other has enriched professional practice and developed individuals’ confidence in terms of playing an active role in research. Our structured reflection has implications for future intervention development research, by highlighting that the provision of a safe, supportive space and nurturing of shared values is key when involving a diverse range of parties. Such contexts promote sustained involvement and therefore have longer term implications for increasing the relevance of the research for those it is aiming to help.